Snood Wire Attachment Enhances Corrosion in Fishing Hooks - G. Gipson Edappazham; Saly N. Thomas; P. M. Ashraf (Fishery Technology, 2022)
Longlining is an important fishing method targeting sharks, tuna, seer fish etc. Fishing line is tied to high carbon steel hook using stainless steel snood wire in order to avoid large carnivorous fishes from biting off the hook. Corrosion is a major problem with hooks and often the hook fails at the eye region where the line is attached to the hook. How the attachment of metallic snood wire affects the hook in terms of corrosion is communicated here. Number 7, Round bent (J shaped) hook was used in this study. Corrosion rate of snood wire-rigged hooks was evaluated by exposing them to accelerated corrosion testing condition (salt spray as per ASTM B117-03-2003). The snood wire rigged hooks recorded substantial weight loss on exposure to salt fog for 300 h compared to control hooks (without snood wire attachment). Correspondingly, snood wire-rigged hooks displayed a corrosion rate of 109.316 mpy (mills per year) against the control hooks witha rate of 60.214 mpy (p<0.05).